2019
DOI: 10.1002/slct.201902838
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to the Synthesis of 2‐Sulfonylaminosubstituted Imidazo[1,2‐a]pyridines via the Cascade Reaction of N‐(1‐aryl‐2,2,2‐trichloroethyl)sulfonamides with 2‐Aminopyridines

Abstract: 2-Aminopyridines react with N-(1-aryl-2,2,2-trichloroethyl)arenesulfonamides in the presence of K 2 CO 3 and DABCO to afford previously unknown 2-sulfonylaminosubstituted imidazo [1,2-a] pyridines. The annulated heterocyclic derivatives are likely formed via dichloroaziridine and α-chloro imidoylchloride intermediates.[a] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…reported the synthesis of 3‐sulfonyl amino‐substituted imidazo[1,2‐ a ]pyridines [159] and other annelated imidazole derivatives from N ‐sulfonyl phenyl dichloro acetal dimines [160] . In continuation of this research, in 2019 they reported the synthesis of 2‐sulfonyl amino‐substituted imidazo[1,2‐ a ]pyridines 203 in the presence of K 2 CO 3 and DABCO from 2‐aminopyridine derivatives 202 and N ‐(1‐aryl‐2,2,2‐trichloroethyl)arene sulfonamides 201 in moderate to good yields [161] . The mechanism involves the formation of the chloroaziridine intermediate A .…”
Section: Development Of Various Methods Towards the Synthesis Of Imid...mentioning
confidence: 98%
“…reported the synthesis of 3‐sulfonyl amino‐substituted imidazo[1,2‐ a ]pyridines [159] and other annelated imidazole derivatives from N ‐sulfonyl phenyl dichloro acetal dimines [160] . In continuation of this research, in 2019 they reported the synthesis of 2‐sulfonyl amino‐substituted imidazo[1,2‐ a ]pyridines 203 in the presence of K 2 CO 3 and DABCO from 2‐aminopyridine derivatives 202 and N ‐(1‐aryl‐2,2,2‐trichloroethyl)arene sulfonamides 201 in moderate to good yields [161] . The mechanism involves the formation of the chloroaziridine intermediate A .…”
Section: Development Of Various Methods Towards the Synthesis Of Imid...mentioning
confidence: 98%